Studi produksi dan kualitas hijauan di lahan padang rumput UPT peternakan Universitas Andalas Padang - Infitria Infitria; Khalil Khalil (Buletin Ilmu Makanan Ternak, 2014)
The present research was aimed to study the quality of forages and productivity of pasture managed bythe teaching farm unit (UPT) of Andalas University by taking samples of forages from 8 paddocks.Samples of forages in fresh form were collected in 5 different sampling points of each paddock by usingquadrant plate meter of 0.5x0.5 m in size. The fresh samples were weighed and then sorted by plantspecies for identification of botanical composition. The samples were then remixed, dried and groundfor chemical analysis. Parameter measured included forage mass production, botanical composition,carrying capacity, DM and nutrient content of CP, CF and ash.Results shown that there were 12 kinds ofspecies grown at the pasture, i.e. 5 gramineae, 4 leguminosae and 3 kinds of browse.Nutrient content ofCP, CF and crde ash ranged from 7.2 to 18.7 %, 37.1 to 47.7 % and 6.6 to 10.0 % DM, respectively.Meanproduction of forages mass in fresh form of about 26.19 t/year with carrying capacities of 2.07AU/paddock. The total carrying capacity of the pasture was about16.1 AU/ha.Keywords: forage mass production, forages quality, pasture